The Iliofemoral Bounce Test: Identifying Hip Capsular Insufficiency - Gabriella Bucci MD; Ryan P. McGovern PhD, ATC; Steven B. Singleton MD; John J. Christoforetti MD (SAGE Publishing, 2022)
Background: Insufficiency of hip capsular structures has recently gained recognition as a cause of pre-arthritic hip pain, leading to hip joint instability and progressive chondrolabral injury. An accurate evaluation of capsular integrity can help orthopedic surgeons plan capsular management prior to hip arthroscopy. Indications: The proposed iliofemoral bounce test is meant to be applied preoperatively for identification of hip capsular integrity when microinstability is suspected or in the setting of revision hip arthroscopy. Technique Description: After induction of general anesthesia and complete muscle relaxation, the patient is placed in a supine figure-four position by placing the foot of the pathologic hip on the contralateral knee. Two examination techniques are performed: (1) The examiner places one hand on the patient's contralateral anterior superior iliac spine and applies consecutive downward pressure in a "rocking" manner to the pelvis; (2) the examiner applies a preload and release force to the flexed knee (examined hip), with the contralateral pelvis stabilized, and observes the response of the knee to this loads. Results: Technique 1: The expected physiologic response in a preserved joint is a "bounce" of the contralateral hip (examined hip), evidenced by an up-and-down movement of the knee in response to the rocking movement applied. This movement reflects the integrity and functionality of the hip capsule ligaments' elastic recoil forces, allowing the hip to remain in a stable state in response to destabilizing forces. In contrast, when capsular insufficiency is present, a lack of bouncing will be observed due to unrestricted external rotation of the hip to constrain the hip joint. Technique 2: In a preserved joint capsule, the knee will return to its preload position, while in capsular insufficiency, no bouncing of the knee will be observed. Discussion/Conclusion: The iliofemoral bounce test is a novel, dynamic, and reproducible examination technique for clinicians to evaluate patient's true hip capsular integrity and for preoperative identification of the proper capsular management, either with a less invasive capsulotomy or performing a capsular closure, plication or even reconstruction, when necessary.